Rabab Pasisia Selatan: Communicating Disasters During the Time of Covid-19 in Indonesia’s Music Industry - Megan Collins (Jurusan Sejarah, Seni, dan Arkeologi, FKIP, Universitas Jambi, 2020)
In this discussion, two new and important developments are exemplified in part, in the 'scene', rabab South Pacisia. The innovations are, firstly: conveying general messages about health issued by Pasisia rabab artisans and secondly, a new long narrative in kaba, the setting during Covid-19, 2020 is not sufficient enough. This year 2020, the craftsmen handyman rabab continues and strengthens his role in West Sumatra, namely an important artist, who is an expert in community communication, entering information about natural disasters, and now the Covid-19 outbreak. His artistic process continues the process of creating information and narratives about natural disasters. So the work of the Pasisia rabab artisan this year continues and combines local, local community entertainment and education about local and global issues in Minangkabau nature. Keywords: Rabab pasisia; Indonesia's Music Industry; covid-19